Assessing the safety culture of care homes: a multimethod evaluation of the adaptation, face validity and feasibility of the Manchester Patient Safety Framework. Issue 9 (19th April 2017) - Marshall, Martin; Cruickshank, Lesley; Shand, Jenny; Perry, Sarah; Anderson, James; Wei, Li; Parker, Dianne; de Silva, Debra
Abstract : Background: Understanding the cultural characteristics of healthcare organisations is widely recognised to be an important component of patient safety. A growing number of vulnerable older people are living in care homes but little attention has been paid to safety culture in this sector. In this study, we aimed to adapt the Manchester Patient Safety Framework (MaPSaF), a commonly used tool in the health sector, for use in care homes and then to test its face validity and preliminary feasibility as a tool for developing a better understanding of safety culture in the sector. Methods: As part of a wider improvement programme to reduce the prevalence of common safety incidents among residents in 90 care homes in England, we adapted MaPSaF and carried out a multimethod participatory evaluation of its face validity and feasibility for care home staff. Data were collected using participant observation, interviews, documentary analysis and a survey, and were analysed thematically. Results: MaPSaF required considerable adaptation in terms of its length, language and content in order for it to be perceived to be acceptable and useful to care home staff. The changes made reflected differences between the health and care home sectors in terms of the local context and wider policy environment, and the expectations, capacity and capabilities of the staff. Based on this preliminary study, the adapted tool, renamed 'Culture is Key', appears to have reasonable face validity and, with adequate facilitation, it is usable by front-line staff and useful in raising their awareness about safety issues. Conclusions: 'Culture is Key' is a new tool which appears to have acceptable face validity and feasibility to be used by care home staff to deepen their understanding of the safety culture of their organisations and therefore has potential to contribute to improving care for vulnerable older people.